2016
DOI: 10.1155/2016/2581876
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effects ofHouttuynia cordataExtract for Oral Infectious Diseases

Abstract: Houttuynia cordata (HC) (Saururaceae) has been used internally and externally as a traditional medicine and as an herbal tea for healthcare in Japan. Our recent survey showed that HC poultice (HCP) prepared from smothering fresh leaves of HC had been frequently used for the treatment of purulent skin diseases with high effectiveness. Our experimental study also demonstrated that ethanol extract of HCP (eHCP) has antibacterial, antibiofilm, and anti-inflammatory effects against S. aureus which caused purulent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 40 publications
(44 reference statements)
0
12
0
Order By: Relevance
“…However, it has been suggested that the use of organic extracts that include ethanol for oral care increases the risks of adverse reactions [ 35 ]. Therefore, a water solution of HC poultice ethanol extract (wHCP) used in our study may be safer than the ethanol based extract (eHCP) [ 36 ]. Our study has examined the properties of dHC, which is simpler to prepare than wHCP and has been used as health-promoting herbal tea without any reported adverse reactions from our interview survey [ 34 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it has been suggested that the use of organic extracts that include ethanol for oral care increases the risks of adverse reactions [ 35 ]. Therefore, a water solution of HC poultice ethanol extract (wHCP) used in our study may be safer than the ethanol based extract (eHCP) [ 36 ]. Our study has examined the properties of dHC, which is simpler to prepare than wHCP and has been used as health-promoting herbal tea without any reported adverse reactions from our interview survey [ 34 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a water solution of HC poultice ethanol extract (wHCP) used in our study may be safer than the ethanol based extract (eHCP) [ 36 ]. Our study has examined the properties of dHC, which is simpler to prepare than wHCP and has been used as health-promoting herbal tea without any reported adverse reactions from our interview survey [ 34 , 36 ]. Previous studies have demonstrated that medicinal plants also exert antiadherence effects against oral microorganisms [ 27 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address this issue, traditional Chinese medicine (TCM) has gradually been used as a substitute therapy with minimal relatively mild side effects. Houttuynia cordata has been shown to prevent oral infectious diseases [5] . Gynostemma pentaphyllum and total glucosides of paeony have been used as treatments for oral lichen planus [6] .…”
Section: Introductionmentioning
confidence: 99%
“…Dental plaque is a multifaceted biofilm that builds up on the surface of teeth, including more than 500 bacterial species. Moreover, it has recently been shown that oral microorganisms can cause other severe or chronic infectious diseases (2,3). The value of mouth and teeth hygiene has been known from ancient times until now.…”
Section: Introductionmentioning
confidence: 99%